Connexin32 ameliorates epithelial-to-mesenchymal-transition in diabetic renal tubular via inhibiting NOX4. (February 2022) - Sun, Xiaohong; Xiao, Haiming; Li, Shanshan; Chen, Rui; Lin, Zeyuan; Yang, Yan; Chen, Zhiquan; Deng, Li; Huang, Heqing
Abstract: Renal tubulointerstitial fibrosis (RIF), characterized by epithelial-to-mesenchymal transition (EMT) of renal tubular epithelial cells (TECs), is the main cause of diabetic renal fibrosis. Oxidative stress plays a pivotal role in the development of diabetic RIF. Connexin32 (Cx32), prominently expressed in renal TECs, has emerged as an important player in the regulation of oxidative stress. However, the role of Cx32 in diabetic RIF has not been explored yet. Here, we showed that adenovirus-mediated Cx32 overexpression suppressed EMT to ameliorate RIF and renal function in STZ-induced diabetic mice, while knockout (KO) of Cx32 exacerbated RIF in diabetic mice. Moreover, overexpression of Cx32 inhibited EMT and the production of extra cellular matrix (ECM) in high glucose (HG) induced NRK-52E cells, whereas knockdown of Cx32 showed the opposite effects. Furthermore, we showed that NOX4, the main source of ROS in renal tubular, was down-regulated by Cx32. Mechanistically, Cx32 down-regulated the expression of PKC alpha in a carboxyl-terminal-dependent manner, thereby inhibiting the phosphorylation at Thr 147 of p22phox triggered by PKC alpha, which ultimately repressed the formation of the p22phox-NOX4 complex to reduce the protein level of NOX4. Thus, we establish Cx32 as a novel target and confirm the protection mechanism in RIF. Graphical Abstract: ga1 Highlights: Anti-EMT effect of Cx32 in renal tubules. Cx32 overexpression represses the formation of the p22phox-NOX4 complex to reduce the protein level of NOX4 and the production of ROS. Cx32 down-regulates the expression of PKCα in a carboxyl-terminal-dependent manner. Cx32 inhibits the phosphorylation at Thr 147 of p22phox triggered by PKCα.